Conflict, Defense Spending and Economic Growth in the Middle East: A Panel Data Analysis - KÜNÜ, Serkan; HOPOĞLU, Sertaç; BOZMA, Gürkan (International Journal of Economics and Financial Issues, 2016)
The relationship between defense spending and economic growth is an active topic of debate for a long time. Defense spending may have negative consequences on the growth performance of developing countries in such conflict-ridden areas as the Middle East. This study is conducted to investigate the effects of defense spending on economic growth in a panel of twelve Middle Eastern countries over the period 1998-2012. The approach suggested by Swamy and Arora (1972) was employed for the empirical study. Findings of the empirical study suggest that defense spending has a negative effect on economic growth, which aggravates during times of internal and external conflicts. Keywords: Defense spending; economic growth; conflict; Middle East. JEL Classifications: E60; F52; H56